Commodity Price Volatility and the Sources of Growth. (IMF Working Papers; Working Paper ;, 2012)
This paper studies the impact of the level and volatility of the commodity terms of trade on economic growth, as well as on the three main growth channels: total factor productivity, physical capital accumulation, and human capital acquisition. We use the standard system GMM approach as well as a cross-sectionally augmented version of the pooled mean group (CPMG) methodology of Pesaran and others (1999) for estimation. The latter takes account of cross-country heterogeneity and cross-sectional dependence, while the former controls for biases associated with simultaneity and unobserved country-specific effects. Using both annual data for 1970-2007 and five-year non-overlapping observations, we find that while commodity terms of trade growth enhances real output per capita, volatility exerts a negative impact on economic growth operating mainly through lower accumulation of physical capital. Our results indicate that the negative growth effects of commodity terms of trade volatility offset the positive impact of commodity booms; and export diversification of primary commodity abundant countries contribute to faster growth. Therefore, we argue that volatility, rather than abundance per se, drives the "resource curse" paradox.